Uso digitales a las comunidades agropecuarias en línea, para la producción e intercambio de conocimientos sobre el manejo de las labores culturales - Del Rosario Troya, Douglas Ariel (2021)
The use of digital today has set a great precedent in agricultural communities, being one of the main methodologies to evolve, know, learn and innovate skills that help the growth of this field. In the same way, the digital evolution in the agricultural area has been recognized as an instrument to increase prosperity, in the same way that food security is guaranteed to the population. In this project, a descriptive analysis is produced about the benefits of digital use in the application of the agricultural sector, technological innovation is specified as an indispensable tool to advance comprehensively towards events that guarantee food sovereignty and security, thus considering technology as an adaptive factor in the agricultural productive sector from the focus of financing for the innovation sector to develop in the agricultural field. The identification of the set of digital instruments that have been added in recent years in the agricultural sector is also reflected.